The Studi Komparasi Pemikiran Syed Naquib Al-Attas dan H.M Rasjidi tentang Konsep Islamic Worldview - Muhammad Fahmi; Suhari Muharam (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
A Comparative Study of Syed Naquib Al-Attas and H.M. Rasjidi's Thoughts on the Concept of Islamic Worldview which examines the problem: differences and similarities of Worldview with the contextual thoughts of HM. Rasjidi's Islamic worldview. Library research method